UI/UX Analysis of Klik Pelalawan Application using Design Thinking Approach and System Usability Scale (SUS) - Ramadhan, Rifky; Anofrizen, Anofrizen; Saputra, Eki; Syaifullah, Syaifullah (Sistemasi: Jurnal Sistem Informasi, 2025)
This study aims to redesign the UI/UX of the Klik Pelalawan application to enhance user comfort. Klik Pelalawan is a mobile application designed as a platform for submitting complaints or aspirations from the public to the local government of Pelalawan Regency. An initial assessment of the application's UI/UX was conducted using the System Usability Scale (SUS) method, accompanied by a survey of 35 residents of Pelalawan Regency. The assessment resulted in a score of 43, indicating that the application's usability level requires improvement. To address this issue, an analysis and redesign process was carried out using the Design Thinking methodology, which consists of five stages: empathize, define, ideate, prototype, and testing. During the testing phase, the redesigned UI/UX was reevaluated by 40 residents of Pelalawan Regency using the SUS method and a questionnaire. The new design achieved a score of 77, signifying that the redesigned UI/UX has successfully improved user comfort for the Klik Pelalawan application.